Experimental and modelling activity on a truck vehicle. (1st January 2003) - Cheli, F.; Resta, F.; Melzi, S.; Donadio, D.
The task is to determine the tyre load spectra of a truck vehicle in terms of hub forces, which will provide the input for a mathematical model for tyre wear evaluation. Two ways have been followed to reach this objective a fully experimental approach, aiming at the direct determination of the hub forces, and a mathematical one, based on multi-body (MB) modelling. An intensive experimental activity has been carried out to set-up a dynamometric hub for the evaluation of direct hub forces and to collect information relevant to the vehicle's dynamic response under typical handling manoeuvres, such as steering-pad and double lane change. The data acquired in these tests have been used to calibrate and validate a truck MB model.